The incidence of rugby-related catastrophic injuries (including cardiac events) in South Africa from 2008 to 2011: a cohort study - Brown, James Craig (BMJ Publishing Group, 2013)
OBJECTIVES: To establish an accurate and comprehensive injury incidence registry of all rugby union-related catastrophic events in South Africa between 2008 and 2011. An additional aim was to investigate correlates associated with these injuries. DESIGN: Prospective. SETTING: The South African amateur and professional rugby-playing population. PARTICIPANTS: An estimated 529 483 Junior and 121 663 Senior rugby union (‘rugby’) players (population at risk). OUTCOME MEASURES: Annual average incidences of rugby-related catastrophic injuries by type (cardiac events, traumatic brain and acute spinal cord injuries (ASCIs)) and outcome (full recoveries—fatalities). Playing level (junior and senior levels), position and event (phase of play) were also assessed. RESULTS: The average annual incidence of ASCIs and Traumatic Brain Injuries combined was 2.00 per 100 000 players (95% CI 0.91 to 3.08) from 2008 to 2011. The incidence of ASCIs with permanent outcomes was significantly higher at the Senior level (4.52 per 100 000 players, 95% CI 0.74 to 8.30) than the Junior level (0.24 per 100 000 players, 95% CI 0 to 0.65) during this period. The hooker position was associated with 46% (n=12 of 26) of all permanent ASCI outcomes, the majority of which (83%) occurred during the scrum phase of play. CONCLUSIONS: The incidence of rugby-related catastrophic injuries in South Africa between 2008 and 2011 is comparable to that of other countries and to most other collision sports. The higher incidence rate of permanent ASCIs at the Senior level could be related to the different law variations or characteristics (eg, less regular training) compared with the Junior level. The hooker and scrum were associated with high proportions of permanent ASCIs. The BokSmart injury prevention programme should focus efforts on these areas (Senior level, hooker and scrum) and use this study as a reference point for the evaluation of the effectiveness of the programme.